Catalytic routes for the conversion of lignocellulosic biomass to aviation fuel range hydrocarbons. (March 2020) - Wang, Hongliang; Yang, Bin; Zhang, Qian; Zhu, Wanbin
Abstract: The catalytic conversion of lignocellulosic biomass to aviation fuel is identified as a key strategy to alleviate high operating costs and serious environmental pollution caused by using petroleum-derived fuels. Aviation fuel with stringent end-use requirements consists of several specific hydrocarbon compositions, and the conversion of lignocellulose to aviation fuel is more challenging than that to other fuels. In this study, the latest cutting-edge innovations on the catalytic conversion of lignocellulose to aviation fuel was summarized. Promising routes for the catalytic conversion of cellulose, hemicellulose, lignin, and their derivatives were elaborated, with emphasis on those catalytic approaches including depolymerization of C–O bonds, formation/rearrangement of C–C bonds, and hydrodeoxygenation (HDO) removal of oxygen-containing functional groups. Innovations on reaction mechanism exploration, catalyst development, solvent screening, and reaction condition optimization were introduced. It revealed that a 100% biomass-derived aviation fuel could be produced by catalytic methods with the full utilization of all lignocellulosic compositions. Straight and branched paraffins in aviation-fuel range could be generated from cellulose and hemicellulose via various intermediates including 5-hydroxymethylfurfural (HMF), furfural, levulinic acid, and γ−valerolactone. The degradation and HDO conversion of lignin could yield aromatics and cycloparaffins in aviation range. The development of hydrothermal stable catalysts for the controllable formation of C–C bonds among platform chemicals from carbohydrates as well as for the efficient HDO conversion of fuel precursors is particularly important. Graphical abstract: Image 1 Highlights: All compositions in lignocellulose can be catalytically converted to aviation fuel. A 100% biomass-derived aviation fuel can be produced by catalytic methods. Paraffins for aviation fuel can be produced from cellulose and hemicellulose. Cycloalkanes and aromatics for aviation fuel can be generated from lignin.